PENGARUH PENDAPATAN PENGELOLAAN DANA TERHADAP LABA BERSIH (STUDI KASUS PT.BANK MUAMALAT INDONESIA TBK) - Midaliyah, Alfa; Yudiana, Yudi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2021)
Fund management is one of the sources of income of Sharia banks. While net profit is the profit obtained by sharia banks after deducting fees. The purpose of this research is to test and analyze the revenue of fund management can affect the net profit of Sharia Bank. The scope of the problem is limited to the management of funds in PT. Bank Muamalat Indonesia, Tbk. The research method used is descriptive quantitative method which is research that analyzes data in the form of statistical figures. The data used in this study was obtained from PT. Bank Muamalat Indonesia Tbk from 2009 to 2013. The analysis techniques used are Simple Linear Regression Analysis and Normality Test. The results showed that fund management revenue significantly affects Net Income. Meanwhile, between fund management revenue and Net Profit there is a strong relationship compared to directly. The point is that if the fund management revenue increases, then the net profit willalso increase.